Maternal sociodemographic factors and neonatal mortality rate in the Maternal Perinatal Institute in 1996 - Villwonte, Wilfredo (2015)
OBJETIVE: To know the neonatal mortality rate at Maternal and Perinatal Institute and the related maternal social and demographic factors. DESIGN: Descriptive and retrospective study. LOCATION: Maternal and Perinatal Institute, Lima-Perú. RESULTS: On the first semester of 1996 there were 210 neonatal deaths. The neonatal mortality rate was 19,7% and the early neonatal mortality rate 13,2%. Regarding the maternal social and demographic factors, 64,5% were pregnant between 20 and 34 years old, 70yo bad higher schooling, 67,5% were in a consensual union, 47,5% had 1 to 4 children, 26,5% have bad abortion and 40,5% did not have prenatal care, 94,51% of pregnancie were high risk pregnancies. CONCLUSION: The mortality rate is high and reflects the low social status of the woman attended at Maternal and Perinatal Institute.